Tappy's team - O'Neill, Nicole; Mawhinney, Art (New York, N.Y. : Modern Pub., 2004)
When he joins a baseball team, Tappy discovers that teamwork is more important than being a star.
First grade.
Keywords: Baseball stories; Teamwork (Sports) -- Juvenile fiction; Swine -- Juvenile fiction; Readers (Primary)